Pengaruh Harga Dan Promosi Terhadap Minat Beli Konsumen Pada Kopi Dari Hati Di Sawangan Depok - Marlinda Sholekhah Salsabila; Sinta Sulistiani (PT. Hasba Edukasi Mandiri, 2025)
This research aims to determine the effect of price and promotion on consumer buying interest in Kopi Dari Hati in Sawangan Depok. The method used is quantitative. The population in this study was 2483 with sample determination using the Slovin Formula, resulting in a sample of 96 respondents. Data analysis uses Validity Test, Reliability Test, Classic Assumption Test, Descriptive Analysis, Simple Regression Analysis, Correlation Coefficient Analysis, Determination Coefficient Analysis, and Hypothesis Testing. The results of the Price variable have a positive and significant influence on Consumer Purchase Interest with a value of tcount > ttable or (9.559 > 1.661) Sig value < 0.05 (0.000 < 0.05). The results of the Promotion variable have a positive and significant influence on Consumer Purchase Interest with a value of tcount > ttable or (7.744 > 1.661) and a value of Sig. < 0.05 (0.000 < 0.05). The results of the variables Price (X1) and Promotion (X2) have a significant effect on Consumer Purchase Interest (Y). Hypothesis testing shows that Fcount > Ftable (51,498 > 3.094) and the Sig. < 0.05 (0.000 < 0.05).